2020
DOI: 10.3892/ijmm.2020.4561
|View full text |Cite
|
Sign up to set email alerts
|

miR‑539 suppresses the proliferation, migration, invasion and epithelial mesenchymal transition of pancreatic cancer cells through targeting SP1

Abstract: MicroRNA (miR)-539 has inhibitory effects on certain types of cancer, but its role in pancreatic cancer (Pca) remains unclear. The present study investigated the effects of miR-539 on Pca, and aimed to determine possible therapeutic targets for the treatment of Pca. The expression of miR-539 in Pca tissues, paired normal adjacent tissues and Pca cell lines (cAPAN-2, BxPc3, cFPAc1, SW1990 and PANc1), and human non-cancerous pancreatic cells (hTRET-HPNE) was determined and compared. The effects of upregulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Targeted inhibition of SP1 by miR-502-5p in gastric cancer cells decreased the levels of cell proliferation, invasion and migration ( 30 ). Moreover, in a previous study, SP1 was found to be targeted by miR-529, thereby suppressing the malignant behaviors and epithelial-to-mesenchymal transition of pancreatic cancer cells ( 31 ). lncRNA-LINC00514 upregulation mediated via SP1 acts as an oncogene in metastatic osteosarcoma by regulating miR-708 expression ( 32 ).…”
Section: Discussionmentioning
confidence: 93%
“…Targeted inhibition of SP1 by miR-502-5p in gastric cancer cells decreased the levels of cell proliferation, invasion and migration ( 30 ). Moreover, in a previous study, SP1 was found to be targeted by miR-529, thereby suppressing the malignant behaviors and epithelial-to-mesenchymal transition of pancreatic cancer cells ( 31 ). lncRNA-LINC00514 upregulation mediated via SP1 acts as an oncogene in metastatic osteosarcoma by regulating miR-708 expression ( 32 ).…”
Section: Discussionmentioning
confidence: 93%
“…Our previous work has brought to light the constitutive expression of Sp1 in PDAC [30][31][32] . Sp1, known to induce EMT by interacting with transcription factors and suppressors such as Twist or Snail, plays a pivotal role in tumor metastasis 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA is a class of endogenous non-coding single-stranded small RNA, which is involved in the regulation of post-transcriptional gene expression by specifically binding to the target genes [ 26 , 27 ]. MiR-539 has been confirmed as a suppressor factor in cancers, and plays an inhibitory role in a variety of cancers, including breast cancer [ 28 ], osteosarcoma [ 29 ], and pancreatic cancer [ 30 ]. However, there are no relevant research reports on miRNA-539-5p in B-ALL at present.…”
Section: Discussionmentioning
confidence: 99%